IMPACT OF ANTENATAL CORTICOSTEROIDS ON FREQUENCY AND MORTALITY DUE TO RESPIRATORY DISTRESS SYNDROME IN PRETERM NEONATES - Shahzad, Fazeela; Umar, Naima (Journal of Ayub Medical College Abbottabad, 2016)
Background: Prematurity is still a major problem for health care services throughout the world. Before the late 1980s, respiratory distress syndrome (RDS) was the primary cause of morbidity and mortality in preterm new-borns. Frequency of RDS and ensuing mortality in infants treated with antenatal steroid is less than those delivered without this therapy. Many pregnant females deliver before term or 37 weeks, hence may be advised this prophylactic therapy without creating significant maternal or foetal side effects. Method: It was a descriptive case-series conducted in the department of obstetrics and gynaecology, unit II of Jinnah Hospital Lahore for a period of 6 months. Results: The study sample of 230 was divided into two groups on the basis of exposure to dexamethasone. RDS was reported 76 (33.0%) cases (preterm neonates) in the study, out of these 26 (22.4%) cases belonged to exposed group and 50 (43.9%) cases belonged to non-exposed group. Mortality due to RDS among all preterm neonates with RDS occurred in total 29 (12.6%) preterm neonates in the study, out of these 5 (4.3%) cases belonged to exposed group and 24 (21.1%) belonged to non-exposed group. Conclusion: Frequency of RDS and mortality due to this disease in group of infants treated with antenatal steroid is far less than the group of preterm new-borns delivered without this therapy. Keywords: Antenatal dexamethasone; effectiveness period; preterm new-borns; RDS; neonatal outcome